2020
DOI: 10.1073/pnas.2000312117
|View full text |Cite
|
Sign up to set email alerts
|

An engineered chimeric toxin that cleaves activated mutant and wild-type RAS inhibits tumor growth

Abstract: Despite nearly four decades of effort, broad inhibition of oncogenic RAS using small-molecule approaches has proven to be a major challenge. Here we describe the development of a pan-RAS biologic inhibitor composed of the RAS-RAP1–specific endopeptidase fused to the protein delivery machinery of diphtheria toxin. We show that this engineered chimeric toxin irreversibly cleaves and inactivates intracellular RAS at low picomolar concentrations terminating downstream signaling in receptor-bearing cells. F… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
64
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(68 citation statements)
references
References 42 publications
4
64
0
Order By: Relevance
“…categorized several colon cancer cell lines for KRAS-dependency based on survival outcomes following KRAS RNAi silencing (36). Published data from our group has shown that the KRAS Indep cell line HCT-116 was highly susceptible to RRSP growth inhibition (27). To extend this finding, the effect of RRSP processing of RAS in KRAS Dep (SW620 and GP5d ) and KRAS Indep (HCT-116, SW1463, HT-29) colon cancer cell lines was tested for relative susceptibility to RRSP ( Fig.…”
Section: Rrsp Inhibits Proliferation and Perk Activation In Colon Canmentioning
confidence: 99%
See 3 more Smart Citations
“…categorized several colon cancer cell lines for KRAS-dependency based on survival outcomes following KRAS RNAi silencing (36). Published data from our group has shown that the KRAS Indep cell line HCT-116 was highly susceptible to RRSP growth inhibition (27). To extend this finding, the effect of RRSP processing of RAS in KRAS Dep (SW620 and GP5d ) and KRAS Indep (HCT-116, SW1463, HT-29) colon cancer cell lines was tested for relative susceptibility to RRSP ( Fig.…”
Section: Rrsp Inhibits Proliferation and Perk Activation In Colon Canmentioning
confidence: 99%
“…Recombinant RRSP-DTB and RRSP*-DTB were expressed in E. coli BL21(DE3) and purified over a HisTrap FF nickel affinity column as previously described (27). Eluted fractions were loaded onto a gravity column containing Strep-Tactin Superflow high capacity resin, followed by SUMOtag removal and size exclusion purification over a Superdex 75 column using ÄKTA protein purifier purification system as previously described (27). For intoxication, colon cancer cell lines were seeded in 6-well plates (~70% confluency) overnight, after which medium was replaced with fresh medium containing either RRSP-DTB or RRSP*-DTB and incubated at indicated timepoints at 37°C in the presence of 5% CO2.…”
Section: Purification and Intoxication Of Rrsp-dtb In Colon Cancer Cementioning
confidence: 99%
See 2 more Smart Citations
“…Sci. USA, we described the development of a biologic chimeric toxin comprising RRSP fused to the translocation and receptor-binding domains of diphtheria toxin (DT B ) [7]. We showed that DT B specifically and efficiently delivers RRSP to cancer cell lines bearing the diphtheria toxin receptor HB-EGF and then abrogates cell viability and proliferation at concentrations as low as one picomolar.…”
mentioning
confidence: 99%